PENGEMBANGAN BAHAN AJAR AKUNTANSI BERBASIS TEKNOLOGI INFORMASI DAN KOMUNIKASI - Aditama, Puput Rio; -, Susilaningsih -; -, Sri Sumaryati (Jupe-Jurnal Pendidikan Ekonomi, 2014)
ABSTRAK            Tujuan penelitian adalah untuk: (1) mengetahui pemanfaatan teknologi informasi dan komunikasi sebagai bahan ajar  akuntansi di SMA N 7 Surakarta saat ini, (2) Menghasilkan produk bahan ajar akuntansi berbasis TIK dengan menggunakan Software Wondershare Quiz Creator, yang layak untuk dijadikan sebagai bahan ajar, (3) Mengetahui kelayakan produk bahan ajar Aku ntansi berbasis TIK dengan menggunakan Software Wondershare Quiz Creator. Penelitian ini merupakan penelitian pengembangan. Prosedur penelitian meliputi 5 tahapan utama: (1) analisis produk yang akan dikembangkan, (2) pengembangan produk awal, (3) Validasi ahli dan revisi, (4) uji kelompok kecil dan revisi, (5) uji kelompok besar dan produk akhir.  Validasi ahli dilakukan oleh seorang ahli materi dan ahli teknologi pembelajaran. Subjek uji coba kelompok kecil dan besar adalah pengajar dan peserta didik kelas XI IPS 2, SMA N 7 Surakarta. Subjek uji kelompok kecil adalah seorang pendidik mata pelajaran ketrampilan akuntansi dan 10 orang peserta didik. Subjek uji kelompok besar adalah 20 orang peserta didik. Berdasarkan hasil penelitian dapat disimpulkan bahwa: (1) pemanfaatan teknologi informasi dan komunikasi sebagai bahan ajar akuntansi di SMA N 7 Surakarta masih sebatas pada penggunaan software Microsoft Power Point sebagai media pembelajaran, (2) produk bahan ajar menggunakan SoftwareWondershare Quiz Creator telah dihasilkan dan dikembangkan, (3) kelayakan produk bahan ajar yang dihasilkan adalah baik, hal ini ditunjukkan oleh penilaian dari ahli materi sebesar 93,93 dan ahli teknologi pembelajaran sebesar 81,25 dari skala 0-100. Pada uji kelompok kecil penilaian dari pengajar sebesar 70,52 dan rata-rata penilaian dari 10 orang peserta didik sebesar 86,3. Pada uji kelompok besar rata-rata penilaian dari 20 orang peserta didik sebesar 86,2.Kata kunci: penelitian pengembangan, teknologi informasi dan komunikasi, bahan ajar akuntansi.ABSTRACT             The objectives of this research are: (1) to investigate the utilization of information and communication technology as the Accounting instructional material at State Senior Secondary School 7 of Surakarta currently; (2) to produce the information and communication technology-based Accounting instructional material product by using Software Wondershare Quiz Creator, which is feasible to be used as an instructional material; (3) to investigate the feasibility of the information and communication technology-based Accounting instructional material product with the use of Software Wondershare Quiz Creator. This research used the research and development (R&D) method. The procedures of the research included five main phases, namely: (1) analysis of product to be developed, (2) the development of initial product; (3) validation by experts and revision; (4) product testing in small group and revision; and (5) product test in large group and final product.  The validation was done by an expert of instructional material and an expert of learning technology. The subjects of product testing both in the small group and in the large group were the teacher and students in Grade XI of Social Science Program 2 of State Senior Secondary School 7 of Surakarta. The subjects of product testing in small group included were a teacher who teaches Accounting Skill subject matter and 10 students whereas the subjects of product testing in the large group were 20 students. The results of the research are as follows: (1) the utilization of the information and communication technology as the Accounting instructional material at State Senior Secondary School 7 of Surakarta  is merely limited to the use of the software of Microsoft Power Point as the media learning; (2) the instructional material product has been produced and developed with the use of Software Wondershare Quiz Creator; and (3) The instructional material product produced is feasibly good to be used as indicated by the results of assessment. The expert of instructional material gives the score of 93.93, and the expert of learning technology gives a score of 81.25 out of the scale of 0-100. The product testing in the small group shows that the teacher gives the score of 70.52, and ten students give the average score of 86.3 toward the product tested. Meanwhile, the product testing in the large group shows that the 20 students give the average score of 86.2 toward the product tested.Keywords:       Research and Development (R&D), information and communication technology, and Accounting instructional material.